A Study of Kasem Adverbs and Adverbials - Nabaarese, J.A. (University of Ghana, 2017)
This thesis explores the different semantic classification of adverbs in Kasem, a Gur language spoken in the Upper East Region of Ghana. It investigates how the different semantic categories of adverbs are formed morphologically and distributed syntactically in the language. The study shows that the different categories of Kasem adverbs can be realized in various forms. Some of them occur in single-word form, others occur in reduplicated form while others are realized in phrasal form. The study further indicates that the different categories of adverbs in the language can also co-occur in the same sentence to perform an adverbial function. I show that like other languages such as English, Ewe and Kinyakyusa; Kasem has a morphological process that allows it to derive adverbs from some nouns. I argue that syntactically, the different categories of adverbs in the language do not exhibit uniform distributional properties. There are some adverbs which occur in sentence final position while there are others that also occur in sentence initial positions. Again, there are other adverbs that are permitted in sentence medial position (between subject and verb/VP). Those adverbs that occur in sentence initial position can either be topicalised or be focused to encode some semantic meaning.
Keywords: Syntactically; Morphological; Semantic classification; Adverbs and Adverbials; Kasem